Implementation of Authentic Assessment: A Case Study in Sanggar Anak Alam Yogyakarta - Olyvia Vita Ardhani (Universitas Negeri Makassar, 2023)
Abstract. This study aims to reveal the implementation of authentic assessment in Sanggar Anak Alam Yogyakarta, including the obstacles encountered by the facilitator and its solution. This is a qualitative study with a case study as the research design to achieve those goals. The data is gathered from focus group interviews and classroom observation. Three facilitators participated in the focus group discussion, and two classes were observed. The finding reveals that the facilitators assess their pupils authentically. It means that the facilitators assess not only the pupils' cognitive development but also their affective and psychomotor development. It can be seen from the pupils’ report cards, which are in the form of a detailed narrative about the result of the pupils’ learning process. However, in implementing the authentic assessment, the facilitators encounter some obstacles. Those obstacles are time constraints and the ability to analyze the data. Nevertheless, the facilitators can overcome these difficulties by managing their time better and getting used to analyzing pupils’ data. It can be concluded that the facilitators in Sanggar Anak Alam have implemented authentic assessments to asses their pupils. Keywords: Authentic Assessment, Facilitator, Implementation